Prevalence of low back pain among gold diggers in Serra Pelada, Pará / Brazil - El Khouri, Marcelo; Corbett, Carlos Eduardo Pereira; Cordeiro, Quirino; Ota, Daniela (Acta Fisiátrica, 2008)
The present study evaluates the prevalence of low back pain in a population of gold diggers in Serra Pelada, a village located in the state of Para, northern Brazil. It was considered one of the largest gold extraction sites in 80s, with approximately 100,000 people involved with gold extraction. Currently, the local population is estimated to be 6,000 inhabitants. A retrospective cross-sectional study was carried out with the data analysis that resulted from a primary medical care evaluation, which was performed in 2002. A total of 1,169 people were treated; 51.7% were males, with a mean age of 41.4± 21.2years; 47% of them reported having worked with gold extraction for a mean time of 10.9 ± 9.7 years. The prevalence of low back pain was 13.7%. When compared to the gold-digger group, the prevalence was 18.2% vs. 10.0% in the non-gold-digger group (p<0.000), thus without statistical significance after logistic regression. Detailed studies are needed to clarify possible associations with low back pain in this population. Perhaps, a screening of old gold diggers who do not live there anymore could help investigate a direct relationship between labor and low back pain.